Science for potters - Bloomfield, Linda (The American Ceramic Society, 2018)
"Science for potters covers those aspects of science which are useful to potters and which help to give a deeper understanding of ceramic materials and processes. Aspects of geology, chemistry, and materials science are covered where relevant to potters. The properties of clays are explained by examining their chemistry and structure. The various rocks and minerals used in glaze making are explored. There are clearly explained science basics including the elements, the structure of the atom, how atoms combine to make compounds, and why some compounds can be used to make colored pigments and glazes. The deeper understanding of materials, their structure, composition, origins, and how they interact will give potters greater control over and new insights into their craft." -- Provided by publisher